2022
DOI: 10.1016/j.gerinurse.2021.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Social participation and depressive symptoms among older adults during the Covid-19 pandemic in Serbia: A cross-sectional study

Abstract: Objectives To determine the predictors and level of social participation and depressive symptoms within the context of isolation during the COVID-19 pandemic and investigate if the residence and type of housing had a moderating role in the relationship between social participation and depressive symptoms. Methods This cross-sectional, comparative, and correlational study was conducted on a sample of 299 participants. Research instruments used in this study included: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
(56 reference statements)
0
12
0
Order By: Relevance
“…41 For example, a systematic review of 51 studies found protective effects of perceived emotional support, instrumental support, and diverse social networks against mental disorders. 42 Egelji c-Mihailovi c et al 43 noted that social participation negatively contributes to depressive symptoms. Thus, mental well-being, in turn, may lead to higher levels of happiness and general wellbeing, 46 particularly in an advancing age.…”
Section: Results In the Context Of What Is Knownmentioning
confidence: 99%
See 1 more Smart Citation
“…41 For example, a systematic review of 51 studies found protective effects of perceived emotional support, instrumental support, and diverse social networks against mental disorders. 42 Egelji c-Mihailovi c et al 43 noted that social participation negatively contributes to depressive symptoms. Thus, mental well-being, in turn, may lead to higher levels of happiness and general wellbeing, 46 particularly in an advancing age.…”
Section: Results In the Context Of What Is Knownmentioning
confidence: 99%
“…For example, a systematic review of 51 studies found protective effects of perceived emotional support, instrumental support, and diverse social networks against mental disorders 42 . Egeljić‐Mihailović et al 43 . noted that social participation negatively contributes to depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies confirm the association between social participation and depressive symptoms. For example Noguchi et al could show that effect as well during the COVID-19 pandemic (12,30). The difference in mental health between participants living in small cities or villages and big cities may be explained due to lower mental health care resources in rural areas compared to big cities (31).…”
Section: Discussionmentioning
confidence: 99%
“…Further, Choi and colleagues (2022) found that participation in clubs or other organized social activities was related to a higher risk of loneliness. Yet, Egeljić-Mihailović and colleagues (2022) demonstrated that social participation was related to fewer depressive symptoms during the pandemic. Choi et al (2021) also found higher levels of social activity, such as volunteering and attending social clubs and religious services, were associated with a reduced risk of depression among older Koreans.…”
Section: Social Contact Social Participation and Emotional Well-beingmentioning
confidence: 99%